The ongoing evolution of humanness: perspectives from Darwin to de Chardin - Buckeridge, J. (South African Journal of Science, 2010)
The nature of humanness is discussed from observations made by Aristotle in 4th-century Greece, through to those of Charles Darwin, Teilhard de Chardin and William Shakespeare. Attempts to define humanness upon a narrow range of criteria, as some have tried, is argued as flawed, for humanness is more elusive than a single or a few demonstrated phenomena. The path that Darwin pursued in determining the place of humans in nature in his book The Descent of Man, and Selection in Relation to Sex is assessed from a 19thcentury perspective; the difficulties he faced, both personally and with the broader public, are reviewed and then evaluated in a modern context. Darwin’s thesis adheres to scientific principles, and is debated, defended and later verified on these principles. This is somewhat at variance to the approach adopted by the priest-scientist de Chardin a century later in his major work, The Phenomenon of Manâ€”in which an attempt is made to reconcile a deep Christian faith with science. De Chardin scores well from a theological viewpoint, but fails on scientific grounds as his thesis moves beyond the realms of empiricism into mysticism. Surprisingly, de Chardin’s predicament of a future wherein human evolution enters a new stage of consciousness through the noosphere (an invisible layer of thought encompassing the globe) has been partially realised through the worldwide web, although the nature of the web is almost certainly not what de Chardin might have anticipated, or desired. Science too fails to answer all, particularly the nature of God. Darwin considered the Creator in several of his works and does not dismiss the concept of a farseeing deity, although we are left with the notion that he died agnostic. Humanness is derived from an elevated moral code and this is reflected in our arts, particularly literature, wherein we may temporally reflect upon quintessential human traits such as mercy. However, expression of the arts is only achievable by the individual being part of a greater whole: the human community, the essence of which is distilled in the Bantu concept of ubuntu, wherein humanness is best realised through the act of living in harmony.